2011
DOI: 10.1186/1471-2164-12-616
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gene expression and protein production rate - a system wide study

Abstract: BackgroundGrowth rate is a major determinant of intracellular function. However its effects can only be properly dissected with technically demanding chemostat cultivations in which it can be controlled. Recent work on Saccharomyces cerevisiae chemostat cultivations provided the first analysis on genome wide effects of growth rate. In this work we study the filamentous fungus Trichoderma reesei (Hypocrea jecorina) that is an industrial protein production host known for its exceptional protein secretion capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 123 publications
5
69
1
Order By: Relevance
“…At the same time, an enrichment of GCN5-related genes among those upregulated under these conditions occurs (Arvas et al 2011). Consequently, chromatin rearrangement is likely to be involved in regulation of enzyme production for carbon acquisition, which is in accordance with studies on correlation of cellulase regulation and epigenetic events Zeilinger et al 2003).…”
Section: Physiologysupporting
confidence: 83%
See 1 more Smart Citation
“…At the same time, an enrichment of GCN5-related genes among those upregulated under these conditions occurs (Arvas et al 2011). Consequently, chromatin rearrangement is likely to be involved in regulation of enzyme production for carbon acquisition, which is in accordance with studies on correlation of cellulase regulation and epigenetic events Zeilinger et al 2003).…”
Section: Physiologysupporting
confidence: 83%
“…A medium-scale approach for transcript analysis in multiple samples was provided by the TRAC (transcript analysis with the aid of affinity capture) system, which allows for simultaneous analysis of 96 samples for around 30 genes (Kataja et al 2006;Rautio et al 2006Rautio et al , 2007. After publication of the fully sequenced genome of T. reesei (Martinez et al 2008) and later also of other Trichoderma spp., construction of full-genome microarrays became possible (Arvas et al 2011;Häkkinen et al 2012;Tisch et al 2011b), followed by large-scale sequencing and transcriptome analysis, which is a standard technique today. Besides genomic and transcriptomic studies, a few proteomic (Adav et al 2012;HerpoelGimbert et al 2008;Jun et al 2011) and metabolomic investigations were reported, although these tools are far less frequently applied.…”
Section: Tools For Genome-wide Investigation and Beyondmentioning
confidence: 99%
“…In a study of T. reesei, gene expression was correlated to protein production rate in chemostat cultures at a range of specific growth rates. 78 This work allowed for the identification of biosynthetic activities with positive and negative effects on protein production and indicated possible regulatory mechanisms in the observed physiological responses.…”
Section: High Yield and Improved Product Secretionmentioning
confidence: 98%
“…Few immune genes showed regulated expression in control larvae which was deregulated due to the parasitic maggot infestation (Table 5). This is possibly to initiate new physiological roles for the gene products indicating functional divergence under the influence of infestation [75,76]. Thus a co-ordinated net-working of proteins of different functions is essential to elicit host defence mechanism against specific parasite attacks [4,77], which necessitate synchronized evolution of immune-associated proteins.…”
Section: Phylogenetic Analysismentioning
confidence: 99%